Service Automation Implementation for Delivering CaaS at the Ministry of Finance of Indonesia - Achmad Farid Rusdi; Bob Hardian; Teguh Raharjo; Tiarma Simanugkalit (Ikatan Ahli Informatika Indonesia (IAII), 2023)
Evaluation is an essential aspect of service improvement. Within the Ministry of Finance, there is an organization responsible for providing IT services to various units and employees. One of the services offered by this organization is cloud computing, which supports the development of information systems. However, there are several challenges related to service fulfillment. For instance, the time required to fulfill a service is relatively long, taking two days, in contrast to public cloud providers, which can deliver their services in minutes. Additionally, there is a potential for human errors in the manual process carried out by the Request Fulfillment Team (RFT) during service delivery. This study aims to explore the design and implementation of automated container service fulfillment, transforming them into self-service products. The author employs the Finite-State Automata (FSA) model to test the input and output of the automation system using seven states and inputs. The results indicate that the container service cycle, when compiled and tested with FSA using predetermined inputs, can generate containers according to user-selected specifications. As a result, the implementation of an automated and self-service model is proposed to reduce delivery time and mitigate potential errors in the container-as-a-service (CaaS) offering.